2007
DOI: 10.1038/sj.eye.6702692
|View full text |Cite
|
Sign up to set email alerts
|

The Dundee University Scottish Keratoconus study: demographics, corneal signs, associated diseases, and eye rubbing

Abstract: Aim To investigate and correlate the corneal, refractive, topographic and familial characteristics of a large cohort with keratoconus. Methods Prospective observational study of 200 consecutive patients presenting with keratoconus during the 4 year-period 1997-2000. Subjects were examined at enrolment and at a final review. Data were collected on demographic characteristics, referral route, symptoms, refractive correction, eye rubbing, family history, medical history, slit-lamp biomicroscopic corneal signs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
164
6
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(208 citation statements)
references
References 43 publications
(42 reference statements)
7
164
6
13
Order By: Relevance
“…The preponderance of men over women has been noted in the most recent studies. 20,[30][31][32][33][34][35][36] Georgiou et al 37 reported a difference of 2.6 times higher in men than women. Some, mainly older studies, have not found differences in the prevalence between genders.…”
Section: Socioeconomic and Demographic Factorsmentioning
confidence: 97%
“…The preponderance of men over women has been noted in the most recent studies. 20,[30][31][32][33][34][35][36] Georgiou et al 37 reported a difference of 2.6 times higher in men than women. Some, mainly older studies, have not found differences in the prevalence between genders.…”
Section: Socioeconomic and Demographic Factorsmentioning
confidence: 97%
“…Diese sind die meist verwendete CL-Type bei KC. Zwei große Studien [9,11] zeigten die häufige Verwendung rigider gaspermeabler CL. Eine Reihe von Linsen-Designs sind verfügbar und bringen einen zufriedenstellenden Tragekomfort.…”
Section: Optische Korrektionunclassified
“…Initiating in puberty, Keratoconus (KCN) often progresses until fourth decade of life [2]. Affecting all ethnic groups equally, KCN usually causes high myopia and irregular astigmatism which results in poor quality of vision [2,3]. Based on disease severity, many treatment modalities exist including glasses and contact lenses for mild to moderate disease [2][3][4] while corneal graft preserved for more advanced disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…Affecting all ethnic groups equally, KCN usually causes high myopia and irregular astigmatism which results in poor quality of vision [2,3]. Based on disease severity, many treatment modalities exist including glasses and contact lenses for mild to moderate disease [2][3][4] while corneal graft preserved for more advanced disease [5]. High costs, need to long follow-ups, long periods for visual rehabilitation, risks of graft rejection or infection, wound dehiscence and suture-related problems make corneal grafts preserved for the last therapeutic choice by many ophthalmologists [6].…”
Section: Introductionmentioning
confidence: 99%